Focal cemento-osseous dysplasia - Mustafa Gumusok; Meryem Toraman Alkurt; Kaan Hamurcu; Dervis Kaan Kilavuz; Emre Baris; Baris Simsek (Wolters Kluwer Medknow Publications, 2014)
Focal cemento-osseous dysplasia (FCOD) is a benign fibro-osseous lesion which changes cancellous bone tissue with each fibrous tissue and cementum-like material, or both together. The teeth that are related to the lesion are vital, and FCOD is generally asymptomatic. FCOD is, usually, found during routine radiographic examination. The etiology and pathogenesis of FCOD are unknown. This lesion is evaluated to be a reactive or a dysplastic process in the periapical tissues. Radiologic images of FCOD change depending on the amount of mineralization. Radiological appearance of FCOD is either only complete radiolocent or only complete radio-opaque or mixed radiolucent, radio-opaque together. In this case report an FCOD is presented, which is located between the first premolar and the second molar on the left side mandible of a 60-year-old female patient. The lesion caused perforation and expansion of alveolar bone. The diagnosis, treatment and 1 year follow-up after surgery are reported.